Cross-Media Industrial Expansion - Take "The Lord of the Rings" as an Example - Xue, Li (International Journal of Global Economics and Management, 2024)
This paper explores the extensive success of "The Lord of the Rings" (LOTR) as a prime example of cross-media industrial expansion. Originating from J.R.R. Tolkien's novels, LOTR has achieved significant commercial and cultural milestones through films, TV series, and video games, generating around $20 billion in revenue. We analyze the principles of trans-media storytelling, where each medium—literature, film, and games—enhances the narrative world. The paper also highlights the fan economy's role in sustaining the brand through community engagement and user-generated content. Challenges in cross-media collaboration, such as content integration and copyright management, are discussed, with suggested solutions including advanced technologies like VR and AR. Case studies like "Pokemon GO" and virtual events in "Fortnite" underscore the innovative potential of cross-industry partnerships. Empirical analysis shows substantial revenue from licensed merchandise and spin-offs, validating the commercial viability of IP cross-field construction. The paper concludes by addressing future trends and challenges, emphasizing strategic planning to maximize the cultural and economic impact of IPs like LOTR.